PENGEMBANGAN KARIER TENAGA KEPENDIDIKAN DI BIRO AKADEMIK DAN KEMAHASISWAAN UNIVERSITAS JAMBI - Krisnaini, Krisnaini; Suryadi, Suryadi; Siswidiyanto, Siswidiyanto (Profit: Jurnal Adminsitrasi Bisnis, 2019)
The pʋrpose of this stʋdy was to determíne career development and identífy inhibíting factors in the career developmẹnt of educatíon personnel at the Jambi University Academic and Student Affairs Bureau. This type of research is descriptive qualitative. With the focus of research as follows the career development of education personnel at the Jambi University Academic and Student Affairs Bureau viewed from aspects of work performance assessment, as well as employee education and training. The inhibiting factor in the career development of education personnel at the Jambi University Academic and Student Affairs Bureau is that the Assessment Center has not been implemented to assess and evaluate the competencies of employees, so that feelings of displeasure and getting unfair treatment can be minimized.